Lichenoid dysplasia- report of 2 cases and review of literature - Shiladitya Sil (Journal of Family Medicine and Primary Care, 2020)
Oral lichen planus (OLP) and oral lichenoid lesions (OLL) have an annual malignant transformation rate of 0.5–2.1%. Lichenoid dysplasia (LD) appears clinically similar to OLP, OLL but histologically harbors atypical cells for which it has a greater potential for malignant transformation. The case reports of two female patients are reported here, which were clinically diagnosed as OLP, later as LD following histopathological confirmation. Both had positive tobacco history and extensive intra-oral lesions. Habit cessation was supplemented by non-steroidal therapeutics with periodic follow-up. There was reduction in the burning sensation, lesion size, and the degree of inflammation of the lesions. Clinical lichenoid like features warrants a biopsy to rule out OLP, OLL from LD. Except for palliation, lesion oriented proper therapeutic treatment should be instituted only after histopathological confirmation.